Short Communication: Egg harvesting and local conservation of Moluccan Scrubfowl (Eulipoa wallacei) in the Maluku Islands, Indonesia - Radios Simanjuntak; MASITAH YUSNIAR; YUNIUS M. SAMALUKANG; FIKTOR IMANUEL BOLEU; ANI MARDIASTUTI; VINCENTIA WIDYASARI; JIHAD SULFANI UDIN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Simanjuntak R, Yusniar M, Samalukang YM, Boleu FI, Mardiastuti A, Widyasari V, Udin JS. 2020. Short Communication: Egg harvesting and local conservation of Moluccan Scrubfowl (Eulipoa wallacei) in the Maluku Islands, Indonesia. Biodiversitas 21: 3018-3024.  This study was conducted at four locations in Central Maluku and North Halmahera, which have been used as nesting ground habitats of the Moluccan Scrubfowl (Eulipoa wallacei), an endemic bird of the Maluku Islands, Indonesia. The objective of this study was to record and analyze the egg harvesting and local conservation of Moluccan Scrubfowl in four locations in the Maluku Islands: Simau, Kao, Haruku, and Kailolo. The results showed that a relatively large number of harvested eggs were found in Simau (Halmahera Island) and Kailolo. In Kailolo, the total number of eggs harvested was 21,707 per year. The local community has the initiative to conserve this bird by establishing local regulations, called sasi. The Haruku community gave a portion of the eggs to Kewang, a customary institution authorized to manage the natural resources, to be hatched semi-naturally around the Kewang House. Likewise, the Salabia youth organization in Simau, together with landowners, developed a semi-natural hatchery for the Moluccan Scrubfowl eggs.